Characterizing the Role of Gds1p in the Saccharomyces cerevisiae Environmental Stress Response - Cotrut, Mihai-Vlad (Université d'Ottawa / University of Ottawa, 2014)
The transcription factors Msn2p and Msn4p are major components of the Saccharomyces cerevisiae environmental stress response. Their transient activation/deactivation is dependent on a regulatory network centering on nucleocytoplasmic shuttling but also includes a range of other mechanisms. The acetyltransferase complex, NuA4 has been implicated in repression of Msn2p yet the mechanism is largely unknown. Gds1p is an uncharacterized yeast protein identified in a recent study as a physical interactor and acetylation target of NuA4. Gds1 protein level is dependant both on NuA4 and environmental stress and our analysis shows it to be involved in the nuclear exclusion of Msn2p in the absence of stress. Unstressed cells lacking GDS1 exhibit increased nuclear accumulation Msn2p and an increase in transcription of the stress reporter gene, HSP12. My work supports a model in which Gds1 and NuA4 can work independently to inhibit the Msn2/4 dependant yeast stress response in the absence of stress.
Keywords: Yeast; Stress Response